The Underlying Mechanisms of Wujiayizhi Granule in Treating Alzheimer's Disease - Xiang, Liu; Lin, Yue; Li, Xianhai; Tang, Qiang; Meng, Fanbo; Chen, Wei (Current Bioinformatics, 2022)
Background: Wujiayizhi granule (WJYZG) is a kind of traditional Chinese medicine, which is used for treating Alzheimer's disease (AD). Although the clinical effect of WJYZG for AD is obvious, its underlying mechanism is still obscure. Objective: Explore the mechanism of WJYZG in the treatment of AD by using bioinformatics methods. Methods: Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), Traditional Chinese Medicine Integrated Database (TCMID) and Encyclopedia Database of Chinese Medicine (ETCM) were used to search the ingredients and targets of WJYZG. DisGeNET, Drugbank, Online Mendelian Inheritance in Man (OMIM), and Terapeutic Target Database (TTD) were used to retrieve the targets of AD. The Cytoscape3.6.1 software was used to construct the interaction network of herbs-ingredients-targets. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the treatment mechanism of WJYZG on AD. Molecular docking was used to validate the interactions between the ingredients and targets. Results: One hundred and thirty-three ingredients were identified from WJYZG. According to the herbingredient- targets network, quercetin, kaempferol, luteolin, anhydroicaritin, and 8-prenyl-flavone were screened out as the key ingredients, which can interact with the core targets encompassing INS, IL6, TNF, IL1B, CASP3, PTGS2, VEGFA, and PPARG. The enrichment analysis indicates that the treatment of AD by WJYZG was through inhibiting inflammation and neurocyte apoptosis, regulating the calcium ion signaling pathway and adjusting INS levels. Conclusion: The underlying mechanisms of WJYZG in the treatment of AD were theoretically illustrated. We hope these results will enlighten the researches on AD.
Keywords: Wujiayizhi granule